A facile synthesis of 2-(2-phenyl-4H-chromen-4-ylidene)-2H-indene-1, 3-diones and related compounds involving an interesting aerial oxidation. Issue 34 (19th August 2015) - Guha, Chayan; Samanta, Swati; Sepay, Nayim; Mallik, Asok K.
Graphical abstract: Abstract: 2-(2-Phenyl-4 H -chromen-4-ylidene)-2 H -indene-1, 3-diones were obtained in good to excellent yields by treatment of 2-hydroxychalcones and indane-1, 3-dione in refluxing toluene in the presence of amberlyst-15 as catalyst in air. The reaction involving 2-hydroxychalcones and cyclopentane-1, 3-dione under the same condition gave 2-(2-phenyl-4 H -chromen-4-ylidene)cyclopentane-1, 3-diones along with 2, 8-dioxabicyclo[3.3.1]nonanes, the relative amount of the products being dependent on the reaction time. Separate experiments have shown that the isolated 2, 8-dioxabicyclo[3.3.1]nonanes are convertible to the other type of products under the applied reaction condition.